Respuesta :

Answer: 16

Step-by-step explanation:

Answer:

If h(x) = 17 + x/6, then h(-18) will equal to 14.

Step-by-step explanation:

We are given an equation...

h(x) = 17 + x/6

When you see h(x), the x represents the value that will be substituted in the equation. "For example, if you have h(9), then 9 would be your x-value." So, we are given h(-18) which means that -18 will be our x-value for this equation. Now that we know this, let's plug in this number into the equation.

h(x) = 17 + x/6

First, substitute the x-value which is -18.

h(-18) = 17 + (-18/6)

Next, divide -18 by 6.

h(-18) = 17 + (-3)

Since -3 is in front of a plus sign, then the equation would be like subtracting 3 from 17 so we will just replace the plus sign (+) with a minus sign (-).

h(-18) = 17 - 3

Now, subtract 3 from 17.

h(-18) = 14

Finally, you have your answer which is 14.